Effect of Pruning on Young Plantations of Acacia catechu Willd, Acacia nilotica (Linn.) Willd Ex Del and Acacia tortilis (Forsk.) Hayne - Luna, R. K.; Kumar, Vijay (Indian Forester, 2007)
One, two and three year old plants of Acacia catechu, A. nilotica and A. tortilis were subjected to no pruning (control), ⅓ pruning and ½ pruning of the total height of the plants. Measurements of height and diameter increment per cent were worked out and analysed statistically. The results show that maximum diameter and height increment was found in one year old plants as compared to two and three year old plants in all species. Clear bole formation was significantly higher in 3 year old plants than one and two year plants. ½ and ⅓rd pruning were equally effective in height increment per cent, whereas ½ pruning was highly significant for diameter increment and clear bole formation than ⅓rd pruning and no pruning. The maximum diameter increment per cent and clear bole formation was attained in A. nilotica as compared to A. tortilis and A. catechu. The results suggest no pruning in one year old plants of Acacia catechu, ⅓rd pruning in A. tortilis and ½ pruning in A. nilotica for one and two year old plants.